Citra Perempuan Pada Produk Rokok di Era Tahun 1930-1950 - Ahmad Muhaimin; Sisca Shammania (Jurnal Studi Sosial dan Politik, 2018)
Analysing cigarette advertisements that existed in ancient times, is an interesting study. Not only because the study is a study of the past, but the adverts in which make the figure of a woman become one of the most important icons in the process of marketing cigarette products. Starting from exposing women's bodies, to the brands of cigarettes taken from women's names. Photos or pictures contained therein have meaning and signs on the sheet, so this is the main object seen by a reader in interpreting the photo. it means that each photo has important points to study. Research entitled: Image of Women in Cigarette Products in the 1930-1950 Era in Indonesia. Aims to read the meaning that is written in it by describing the socio-cultural situation, maybe the politics around it or the ideological meanings contained therein. The methodology used in this research is descriptive, with a qualitative approach. The meaning referred to in this study is the meaning based on analysis using Roland Batrhes's Theory of Semiotics which is the meaning of denotation, connotation and myth. The meanings will appear on every sign that is captured by the reader through the five senses that are interpreted based on knowledge, and also the existing history of this study focuses on the past. The number of photos to be analyzed consists of three photos, which will be divided into several sections. With one photo to be broken down into objects, it aims to make it easier to read the meanings and meanings of denotations, the myths that are in it. As well as knowing the intention of the cigarette ad image maker, so that it can contain the formation of the image formed. There are 3 images formed from the results of a study of the advertisement photos of cigarette products, these are: image frames, imagery of fusion, and social imagery.